(untitled) (Società e diritti, 2022)
The Myth of a united Europe lasted from the fall of Rom to the present day; but a real European unity there was only in the Carolingian period, because subsequently the national States ware formed. Modern ideology aims to bild a unitary state for all the peoples of Europe; but each people has the right to self-determination and cultural identity, and a compulsory merger would infringe the fundamental rights of national authorities..